USING SISPUKOM FOR AN INTEGRATED LIBRARY AND INFORMATION SYSTEM : THE EXPERIENCE OF ITM, JO LIBRARY, MALAYSIA - Yaacob, Raja Abdullah; Abdullah, Nor Aziah (2001)
Recent technological advances have affected the management of library systems in Malaysia. Currently, the number of libraries and information centres that are gearing towards library automation and application of new technologies are increasing. The ITM, JO joins the race by using the only available local software package known as SISPUKOM. The library, though considered as a medium-sized, is moving fast towards this direction and to date has opened the CD-ROM services to its patrons. The application of IT is not static but dynamic, and evolving along the technological changes and environ0-mental needs. Two main factors are emphasized, namely the use of local software package; and the process of decision, planning and implementation of the system, and the problem associated with the project. While libraries affiliated with universities or other academic institutions are likely to be reasonable in the size of their collection, building, staffing, and budgeting, the great majority of libraries and information centres in Malaysia in particular and elsewhere in Asia in general are still medium in terms of their size. How this library tackled the planning and implementation programmes may have similar implication on other libraries of the same size anticipating to automate. Decision on using a local package was considered seriously and such experience is worth noting too. Highlighted also in this paper is the impact of the new application of IT on several areas of library and information services. Subsequently, the process of computerization affect a great deal on the restructuring of staff duties, physical structure and training for both staff and patrons.